Mr. Smith goes to Washington - Buchman, Sidney, 1902-1975; Stewart, James, 1908-1997; Arthur, Jean, 1900-1991; Rains, Claude, 1889-1967 (Culver City, Calif. : Sony Pictures Home Entertainment, 2012)
Stewart plays a freshman senator in Washington, D.C. who becomes involved in political infighting when a project of his is undermined by unscrupulous others who want to build a dam.
Originally released as a motion picture in 1939.
Features: commentary by Frank Capra Jr.; Frank Capra Jr. remembers-- "Mr. Smith Goes To Washington", Vintage advertising gallery, original theatrical trailer.
Jean Arthur, James Stewart, Claude Rains, Edward Arnold, Guy Kibbee.
MPAA rating: Not rated.
DVD, Dolby digital stereo.
In English with optional English, Japanese, Korean, or Portuguese subtitles.
Keywords: Legislators -- United States -- Drama; Political corruption -- United States -- Drama; Politcal films; Fiction films; Video recordings for the hearing impaired; Feature films